2014
DOI: 10.1007/s00442-014-3040-5
|View full text |Cite
|
Sign up to set email alerts
|

Predicting reproductive success from hormone concentrations in the common tern (Sterna hirundo) while considering food abundance

Abstract: In birds, reproductive success is mainly a function of skill or environmental conditions, but it can also be linked to hormone concentrations due to their effect on behavior and individual decisions made during reproduction. For example, a high prolactin concentration is required to express parental behaviors such as incubation or guarding and feeding the young. Corticosterone level, on the other hand, is related to energy allocation or stress and foraging or provisioning effort. In this study, we measured ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 58 publications
1
40
2
Order By: Relevance
“…Other studies of seabirds have found clear effects of year on reproductive success (e.g., Becker 1998, Quilllfeldt 2001, Golet et al 2004) and, in a previous study, we also showed that reproductive success was significantly different between years in this Common Tern colony (Riechert et al 2014a). However, sample sizes were much higher in these studies.…”
Section: Reproductive Success and Nest Attendancementioning
confidence: 80%
See 3 more Smart Citations
“…Other studies of seabirds have found clear effects of year on reproductive success (e.g., Becker 1998, Quilllfeldt 2001, Golet et al 2004) and, in a previous study, we also showed that reproductive success was significantly different between years in this Common Tern colony (Riechert et al 2014a). However, sample sizes were much higher in these studies.…”
Section: Reproductive Success and Nest Attendancementioning
confidence: 80%
“…There have been a number of studies conducted in this colony specifically to investigate the influence of hormones on behavior and reproductive success, which form a basis for this work. Riechert et al (2014a) showed that prolactin levels increased with breeding experience in young Common Terns, which was correlated with improved success during initial breeding attempts. Overall, increased reproductive output was linked with high prolactin levels and slightly increased baseline corticosterone, especially in males (Riechert et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, only three studies have examined the relationship between circulating prolactin and environmental conditions in parent birds. First, Riechert et al (2014a) found that prolactin levels were not correlated with food abundance in Common terns although prolactin titers were particularly low during two years of low food availability. Second, Leclaire et al (2011) found that prolactin levels were not affected by an experimental handicap (i.e.…”
Section: Environmental Conditions and Prolactin Levelsmentioning
confidence: 97%